South Africa’s Nuclear-Tipped Ballistic Missile Capability - United Nations Office for Disarmament Affairs (United Nations, 1992)
This report examines South Africa's nuclear and missile programmes in an attempt to establish the facts about its capabilities and to the extent possible, to determine its intentions. The analysis cannot be divorced from, nor seen in isolation from, the political context. It addresses the effects the recent political evolution in South Africa and its relations with its neighbours have had on its nuclear programme? Considering the secrecy surrounding nuclear programmes the information presented in this publication is impressive.